The Application Of Krashen’s Hypothesis In Teaching Speaking In Elementary School - Pratiara Amalya Fasa; Indah Purnama Dewi; Masagus Firdaus (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores the application of Krashen’s Input Hypothesis (i + 1) in enhancing elementary school students’ speaking skills through verb-based learning. The focus is to examine how comprehensible input supports the acquisition of English verbs and their use in simple sentences. The research employed a descriptive qualitative design involving 27 third grade students at SD Manggala Palembang. Data were gathered through observation, interviews, and speaking performance tasks. Findings indicate that when students were first introduced to verbs through songs and actions (e.g., run, jump, sing) and later guided to use them in sentences (e.g., “We are running”, “My teacher is teaching English”), their confidence and fluency improved significantly. The study concludes that Krashen’s Input Hypothesis effectively promotes natural speaking development by offering meaningful, understandable, and enjoyable language exposure.